State negative affect in relation to loss-of-control eating among children and adolescents in the natural environment. (1st November 2022) - Parker, Megan N.; Tanofsky-Kraff, Marian; Crosby, Ross D.; Shank, Lisa M.; Kwarteng, Esther A.; Loch, Lucy K.; Faulkner, Loie M.; Haynes, Hannah E.; Gupta, Suryaa; Fatima, Syeda; Dzombak, Jesse W.P.; Zenno, Anna; et al.
Abstract: Affect regulation theory proposes that loss-of-control (LOC)-eating is preceded by increases and followed by decreases in negative affect (NA), but empirical tests of this theory among pediatric samples in the natural environment are needed. Using an ecological momentary assessment approach, we conducted post-hoc analyses to examine LOC-eating severity reported during post-meal surveys in relation to the intensity of composite NA and NA components (anger, anxiety, depression, guilt) throughout the day for two weeks in a cohort of healthy children and adolescents. Multilevel models tested the associations among LOC-eating severity and NA components reported at pre-meal surveys (t-1), post-meal surveys (t), and lagged post-meal surveys (t+1). Models were adjusted for sex, age, race/ethnicity, height, fat mass, socioeconomic status, and time between the occurrence and report of eating episodes; post-meal analyses were also adjusted for pre-meal NA. Participants age 8–17 ( N = 100; 55% female; 45% male; 12.83 ± 2.73y; 24% with overweight/obesity) recorded 2410 eating episodes. Pre-meal composite NA and NA components were not associated with LOC-eating severity at the subsequent meal. LOC-eating severity was positively associated with post-meal depression (β = 0.042, 95% CI = 0.007, 0.076) and guilt (β = 0.056, 95% CI = 0.017, 0.095), but not composite negative affect, anger, or anxiety. The positive association among LOC-eating severity and guilt persisted in lagged post-meal analyses (β = 0.075, 95% CI = 0.021, 0.128). Contrary to affect regulation theory and laboratory data, but consistent with prior ecological momentary assessment data in children and adolescents, pre-meal NA was not linked to subsequent LOC-eating. Increased guilt following meals may be a mechanism for the development of exacerbated disordered eating. Longitudinal studies may elucidate how NA is implicated in the etiology of pediatric eating disorders.